A Constructivist Grounded Theory of Staff Experiences Relating to Early Mobilisation of Mechanically Ventilated Patients in Intensive Care. (4th February 2022) - Clarissa, Catherine; Salisbury, Lisa; Rodgers, Sheila; Kean, Susanne
Early mobilisation of mechanically ventilated patients has been suggested to be effective in mitigating muscle weakness, yet it is not a common practice. Understanding staff experiences is crucial to gain insights into what might facilitate or hinder its implementation. In this constructivist grounded theory study, data from two Scottish intensive care units were collected to understand healthcare staff experiences relating to early mobilisation in mechanical ventilation. Data included observations of mobilisation activities, individual staff interviews and two focus groups with multidisciplinary staff. Managing Risks emerged as the core category and was theorised using the concept of risk. The middle-range theory developed in this study suggests that the process of early mobilisation starts by staff defining patient status and includes a process of negotiating patient safety, which in turn enables performing accountable mobilisation within the dynamic context of an intensive care unit setting.